Extracellular Vesicles from 3D Engineered Microtissues Harbor Disease‐Related Cargo Absent in EVs from 2D Cultures. Issue 5 (22nd April 2021) - Millan, Christopher; Prause, Lukas; Vallmajo‐Martin, Queralt; Hensky, Natalie; Eberli, Daniel
Abstract: Engineered microtissues that recapitulate key properties of the tumor microenvironment can induce clinically relevant cancer phenotypes in vitro. However, their effect on molecular cargo of secreted extracellular vesicles (EVs) has not yet been investigated. Here, the impact of hydrogel‐based 3D engineered microtissues on EVs secreted by benign and malignant prostate cells is assessed. Compared to 2D cultures, yield of EVs per cell is significantly increased for cancer cells cultured in 3D. Whole transcriptome sequencing and proteomics of 2D‐EV and 3D‐EV samples reveal stark contrasts in molecular cargo. For one cell type in particular, LNCaP, enrichment is observed exclusively in 3D‐EVs of GDF15, FASN, and TOP1, known drivers of prostate cancer progression. Using imaging flow cytometry in a novel approach to validate a putative EV biomarker, colocalization in single EVs of GDF15 with CD9, a universal EV marker, is demonstrated. Finally, in functional assays it is observed that only 3D‐EVs, unlike 2D‐EVs, confer increased invasiveness and chemoresistance to cells in 2D. Collectively, this study highlights the value of engineered 3D microtissue cultures for the study of bona fide EV cargoes and their potential to identify biomarkers that are not detectable in EVs secreted by cells cultured in standard 2D conditions. Abstract : Engineered 3D microtissues secrete extracellular vesicles (EVs) with more diverse molecular cargo than 2D cultures. Numerous cancer‐specific proteins found in 3D‐EVs are absent in 2D‐EVs from the same cell types. A putative EV biomarker exclusively found in 3D‐EVs, GDF15, is validated as a bona fide EV protein, for the first time, using imaging flow cytometry.